Survey on AI-Assisted Power Transmission Line Fault Detection - Yue Zhang; Yonghui Xu; Lizhen Cui (International Journal of Crowd Science)
As the main channel for energy transmission, the stable operation of transmission lines is crucial for energy supply and economic development. However, various faults such as short circuits, overloads, and poor grounding contacts inevitably occur during the operation of transmission lines. These faults not only affect the power quality but also cause equipment damage, and even lead to fires and safety accidents. Therefore, the research on transmission line fault detection technology is of great significance. This paper analyzes the advantages and disadvantages of existing artificial intelligence-assisted transmission line fault detection technologies, aiming to provide valuable references for the comprehensive realization of intelligent transmission line fault detection and promote further development in this field.